Variação acústica de F2 da vogal [i] em contexto de palatalização das consoantes oclusivas alveolares em falas de dois municípios baianos - Correia, Adilson da Silva (2023)
The investigation, in this doctoral dissertation, develops analysis of the formant F2 of the vowel [i], in the context of palatalization of dentoalveolar stop consonants, in Brazilian Portuguese (BP). Through an experimental methodology in Acoustic Phonetics and based on the SourceFilter Theory of speech production (FANT, 1960), the study undertook speech collection in two municipalities in Bahia, in order to generate data on the vowel [i] in the context of nonpalatalized consonants [t, d], in Nova Soure, and palatalized [tʃ, dʒ], in Alagoinhas, from eight subject-participants, four men, two from Nova Soure and two from Alagoinhas and four women, two from Nova Soure and two from Alagoinhas. Based on the argument that the F2 of the vowel [i] in palatalized consonants is smaller than in palatalized, the study demonstrated, through central and dispersive measures of F2, the data of formant measures in palatalized consonants represents statistically and significantly differences in relation to non-palatalized. In the sample of women, this difference is much more marked than in the sample of men. In addition, we observed how the standard normal curve shifts asymmetrically and how the data aggregates around the central measures through coefficients of skewness. The conclusions of the study tend to confirm the hypothesis that the F2 of palatalized consonants is smaller than non-palatalized. This argument strengthens the hypothesis about the anteroposteriority of the vowel [i] in contexts of palatalization of dentoalveolar stop consonants, confirming the argument that the vowel is more anterior to stops and more posterior to affricates.